Teaching Leadership Using Concept Map: A Case Study for the Relationship Between Manager and Leader - Soerjaningsih, Th. Widia (Journal the Winners: Economics, Business, Management, and Information System Journal, 2004)
Usually teaching using concept map, is able to make everything clearer than if we use descriptive approach. But we cannot use concept map in all subjects. Teaching in science and mathematics subject can easily use concept map but not in teaching art. Leadership subject is an art, but in some cases we can use concept map too. In this case, we are focusing at the topic: â€œRelationship between Manager and Leaderâ€.